TEXTURE ANALYSIS OF MAGNETIC RESONANCE T1 MAPS AND EXTRACELLULAR VOLUME IN HEART FAILURE COMPARED WITH NORMAL CONTROLS - Chau , Thi Ngoc Anh; Ming, Ming - Ting Wu (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2021)
Objective: To assess the T1 and extracellular volume (ECV) maps of left ventricle (LV) of patients with non-ischemic heart failure (NIHF) by cardiac MRI Materials & Methods: This retrospective study included 23 NIHF (mean age = 48.1 years, 12 M), 25 matched healthy control (HC) performed CMR on 3T scanner (Skyra, Siemens). NIHF was diagnosed by echocardiography, coronary artery angiogram and myocardial perfusion SPECT. Native T1 map was obtained by modified MOLLI 5-3 sequence and ECV was calculated 12 min. after GBCA 1.5 dose with 4-3-2 sequence on 4C view. Texture analysis was performed with LIFEx(www.lifexsoft. org). We also measured the wall thickness (WT) and outer diameter (OD) of LV. Results: NIHF had larger OD of LV (78 +/- 16 mm) than the HC (57+/-6 mm) (P,0.001) while the WT had no difference (10.9 +/- 3.4 mm vs. 10.2 +/- 2.6 mm, p=0.41). Native T1 was significantly higher in NIHF patients (1310+/- 48 ms) compared to HC (1208+/- 72 ms) (p<0.001), while the ECV showed no difference (29+/- 4.8% vs. 27+/- 5%, p=0.30). The texture analysis of T1 and ECV map¬¬¬s showed no difference in the first-order textures and had significant difference in several second-order textures, such as GLRLM, GLZLM. There was inverse correlation of ECV and WT of LV in NIHF (r=-0.61, p=0.002). Conclusions: In NIHF with preserved WT of LV, texture analysis of T1 and ECV maps showed difference in the mean value of native T1 and texture features, which is promising as a base for machine learning with future larger cohort.